Deradicalization to Reintegration: Examining Post-Release Dynamics of Former Terrorism Offenders in Bengkulu - I Wayan Bayuna (DAWUH : Islamic Communication Journal, 2026)
This research, using empirical data from Bengkulu Province, revisits the implementation of deradicalization policies in Indonesia by creating an integrated governance model based on the dynamics of reintegration of former terrorist convicts. This study discusses the ongoing fragmentation in deradicalization programs, where socio-economic reintegration, psychosocial rehabilitation, and ideological disengagement are still poorly coordinated across various institutions. Data were collected from 30 informants representing government agencies, academics, civil society, media, corporate actors, and former terrorist convicts using a qualitative descriptive design and an interactive analytical approach from Miles, Huberman, and Saldaña (2014). The findings demonstrate that the effectiveness of deradicalization is shaped by three interdependent dimensions: (1) cognitive transformation through educational interventions, (2) psychosocial recovery through rehabilitation processes, and (3) structural reintegration through social inclusion and economic empowerment. However, significant implementation gaps persist, particularly in inter-agency coordination, sustainability of economic support, and the persistence of social stigma toward former offenders. The results of this study offer the Integrated Penta-helix Deradicalization Governance Model (IPDGM), a unique theoretical framework that combines social identity theory, collaborative governance theory, and policy implementation theory. By shifting the focus of analysis from state-centered methods to multi-actor governance, this model improves the literature and provides policymakers in Indonesia with a more flexible and comprehensive framework for implementing deradicalization policies.